Single polymer fiber–based ultrasensitive and multifunctional flexible microsensor via arthropod-inspired crack-helix coupling - Zixun Chen; Ye Zhang; Huaizhi Liu; Zhiwei Li; Jiuyang Zhang (Proceedings of the National Academy of Sciences, 2026)
Flexible microsensors featuring miniature dimensions (< 100 μm), superior sensitivity [Gauge factor (GF) > 10 3 ], and phenomenal environmental stability (> 10 4 uses) have been broadly applied in modern soft electronics such as implantable health monitoring and soft robotics. However, it is quite challenging to integrate these distinguished features in a microdevice considering the extremely limited space for the complicated fabrication and complex functionalities. Inspired by microscale sensing systems in arthropods, this work presents a unique crack-helix soft microsensor (CHMS) within a single polymer microfiber. This microdevice successfully combines the structural advantages of both slit and hair sensors in arthropods through convenient depositing a thin layer (thickness: 2.5 μm) of biphasic liquid metals on a single microfiber (diameter: 80 μm). The microsensor presents unique frequency detection capability as arthropods (resolution: 0.01 Hz, > 1,088 Hz), ultrahigh sensitivity (GF > 2,711 ± 119), astonishing detection limit (0.05% strain and 0.2 mN), and excellent sensing durability (over 50,000 cycles), which are among the best of currently reported soft sensors. Furthermore, analogous to natural arthropods, CHMS shows different multifunctional environmental perception capability to precisely recognize subtle vibration under water or ground (amplitude < 70 μm) and extremely rarefied airflow (ultralow mass flux: 2.2 × 10 −4 g/s·cm 2 ).